Experiences of Patients and Families Living with Krabbe Disease - Yuta Koto PhD; Wakana Yamashita MSN; Kumiko Kitamura MSN; Norio Sakai PhD (Journal of Patient Experience)
The challenges faced by patients with Krabbe disease remain unelucidated. This study aimed to identify these challenges and facilitate the development of methods for assessing the quality of life. This qualitative descriptive study used in-person or online semistructured interviews from March to December 2022 using a qualitative content analysis approach. Data were collected from one patient each for the late infantile, juvenile, and adult types of Krabbe disease. In total, 249 codes were extracted from the verbatim transcripts and integrated into 40 subcategories and eight categories. The categories were integrated into three themes: the impact of symptoms on daily life, challenges for healthcare systems, and challenges faced by family members. Patients experienced physical symptoms, social life challenges, and medical care difficulties. Additionally, families felt burdened caring for these patients. In conclusion, support systems for patients and their families during treatment and in their living environments should be developed to aid in managing these challenges. Moreover, a comprehensive scale that accurately reflects the social challenges faced by these patients and their families is needed.